Study of protection policy on cultivated land in economy fast developing area - FANG Bin; WU Ci-fang (浙江大学学报. 农业与生命科学版, 2006)
The article Analyses the difficulty of the protection of cultivated land based on understanding the contradiction between fast increasing of economy and lacking of cultivated land resources in economy fast developing area. At same time, It proposed the protection strategy in the long future and countermeasure in the near future.